2004
DOI: 10.1096/fj.03-0645rev
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenases: new forms, new inhibitors, and lessons from the clinic

Abstract: The beneficial actions of nonsteroidal anti-inflammatory drugs (NSAIDs) have been linked to their ability to inhibit inducible COX-2 at sites of inflammation, and their side effects (e.g., gastric damage) to inhibition of constitutive COX-1. Selective inhibitors of COX-2, such as celecoxib, etoricoxib, lumiracoxib, rofecoxib, and valdecoxib have been developed and the greatest recent growth in our knowledge in this area has been come from the clinical use of these compounds. Although clinical data indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
390
1
25

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(425 citation statements)
references
References 149 publications
(127 reference statements)
9
390
1
25
Order By: Relevance
“…In human keratinocytes, PI3K regulates UV-B light induced cyclooxygenase-2 (COX-2) expression through activation of AKT and consequential inhibition of glycogen synthase kinase 3β (GSK3β) (Tang et al, 2001;Bachelor et al, 2005;Sheu et al, 2005;Wu et al, 2005). COX-2 gene responds to a diverse range of stimuli from growth factors or cytokines to physical or chemical stress by increasing expression (Smith, 2000;Hinz and Brune, 2002;Turini and DuBois, 2002;Warner and Mitchell, 2004). Several signaling transduction pathways have been shown to regulate COX-2 gene expression, including the Mitogen-Activated Protein Kinases (Smith, 2000), Protein Kinase A (Choudhary et al, 2004;Pino et al, 2005) or Protein Kinase C (Xuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In human keratinocytes, PI3K regulates UV-B light induced cyclooxygenase-2 (COX-2) expression through activation of AKT and consequential inhibition of glycogen synthase kinase 3β (GSK3β) (Tang et al, 2001;Bachelor et al, 2005;Sheu et al, 2005;Wu et al, 2005). COX-2 gene responds to a diverse range of stimuli from growth factors or cytokines to physical or chemical stress by increasing expression (Smith, 2000;Hinz and Brune, 2002;Turini and DuBois, 2002;Warner and Mitchell, 2004). Several signaling transduction pathways have been shown to regulate COX-2 gene expression, including the Mitogen-Activated Protein Kinases (Smith, 2000), Protein Kinase A (Choudhary et al, 2004;Pino et al, 2005) or Protein Kinase C (Xuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the classical NSAIDs have been reappraised and turned out to be mostly COX-1 selective, which thus reflected their tendency to cause gastrointestinal side effects. However, the positive effects of selective COX-2 inhibition have subsequently been questioned, as any lesser rate of gastrointestinal adverse effects may have been outweighed by negative effects such as increased risk of cardiovascular events [11] . As regards to colorectal surgery, recent retrospective clinical studies have also indicated a negative effect on anastomotic healing [12][13][14] , as well as some, but not all, experimental investigations [15][16][17] .…”
Section: Commentary On Hot Articlesmentioning
confidence: 99%
“…They exert these effects mostly through inhibiting the production of prostaglandins (PGs) and leukotrienes (LTs) by the cyclo-oxygenase (COX) and 5-lipoxygenase (5-LOX) enzymes, respectively. [33][34][35] Most NSAIDs primarily inhibit the activity of COX enzymes. Although some also inhibit LOX enzymes, for currently licensed feline drugs this is generally short-lived in comparison with COX inhibition, and evidence of additional clinical efficacy from this is lacking.…”
Section: Nsaids and Cyclo-oxygenase/ Lipoxygenase Inhibitionmentioning
confidence: 99%
“…[36][37][38] Two distinct COX isoforms (COX-1 and COX-2) have been identified as being responsible for the production of prostaglandins (Fig 7). 35 A third isoform has also been identified, initially known as COX-3, now described as a splice-variant of COX-1, which seems to have a role in the central control of pain. 38 Phospholipase A 2 is the rate-limiting enzyme that initiates the COX pathway by liberating arachidonic acid (AA) from membrane-bound phospholipids.…”
Section: Nsaids and Cyclo-oxygenase/ Lipoxygenase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation